Using Duolingo Application In Learning Vocabulary: A Descriptive Qualitative Study At The Fifth Grade Of An Elementary School In Sumedang - Rahma Sakina; Riyanti Sri Astuti (Universitas Subang, 2024)
The use of technology in education, particularly in language learning, has become increasingly prevalent. Among the numerous language learning applications available, Duolingo has gained significant popularity. The research titled